The impact of cumulative adversity on depression among older adults: a cross-national perspective - Georgia VERROPOULOU; Eleni SERAFETINIDOU; Cleon TSIMBOS (European Journal of Geography)
The study considers the effects of accumulation of disadvantage over the life course in three key domains of life, health, socioeconomic status and adverse experiences, on later life depression, focussing on differentials between genders and across European populations. Information on 23816 persons aged 50+ has been used from wave 2 (cross-sectional material) and wave 3 (retrospective) of the Survey of Health Ageing and Retirement in Europe (SHARE). Cumulative health disadvantage seems to have the greatest relative effect for both sexes and across Europe. Males are more affected by poor health and socioeconomic adversity whereas for females, adverse experiences have a stronger effect. In several countries cumulative adverse experiences are more important compared to cumulative socioeconomic disadvantage; the first seems of greater consequence in Poland and Ireland while the latter mainly in Southern Europe. The study shows that accumulation of disadvantage over the life course significantly predicts depression across European countries.